The reform of the foster care system. Assumptions, reality, perspectives. - Andrzej Chudnicki (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The aim of the article is to present changes that underwent in the twenty-first century in the Polish institutional child care system. The author discusses changes in educational care facilities in respect of worldwide tendencies in the field of transformation from institutional care to the care provided at a local community level. The article shows the effects of current legal and organizational solutions. Lack of effective solutions in the sphere of social policy which causes the increasing numbers of the juveniles in the custody of the courts is shown as a cause of the constant (not diminishing) need for institutional care. The article also suggests a different organization of the institutional foster care system which includes, first of all, the needs of children placed in it.